An investigation into the use of functional approach to translation in a grammar course at the university of danang - university of foreign language studies - Nguyễn Thị Cát Phượng (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Translation has been reemerging in language teaching and its use is of great interest to scholars in the field. More evidence is needed to demonstrate its effectiveness in language learning. This research aims to examine the applicability of the functional approaches to translation for English language teaching, focusing on investigating the effect of functional approaches to translation on students’ awareness of Reported speech. This mixed research presents data from students’ test results and interviews among 34 students and 3 teachers from University of Foreign Language Studies - The University of Danang. The research findings showed functional approaches to translation improved students' post-test results, compared to their pretest results. In addition, students' awareness of functional approaches to translation or contextual factors of translation was also improved significantly. Through interviews, students demonstrated favorable attitudes towards the functional approaches to translation in their language learning process. In addition, the results of interviews with teachers showed that they had different opinions regarding the use of translation. Although teachers expressed a lack of interest in translation, they still used translation as a tool to explain grammatical structures that could be confusing to students. This research indicates the feasibility of the functional approaches to translation in the teaching of grammar. Further research is needed in the application of functional approaches to translation as a useful tool in language teaching in general or grammar teaching in particular.